Is There Life? Is There Spirit? Debating Belief and Being a Good Christian in Watchman Nee’s ‘Little Flock’ - Christine Lee; Yujing Ma; Jianbo Huang (Religions, 2023)
Christian, especially Protestant, identity is often framed through the lens of belief, particularly belief understood as an interior orientation. Through an examination of the non-denominational Protestant group, the ‘Little Flock’, founded by Watchman Nee in the early 20th century, we trace enduring aspects of Little Flock theology in contemporary Chinese Protestant practice. In particular, we attend to conceptions of and debates surrounding belief and how to determine the quality of one’s faith—whether or not one might be considered not just a Christian, but a ‘good’ one.